Prim̆. [i.e. Prim̆sīpala] Tejā Siṅgha dī wārataka : Sahija subhā de ādhāra te - Jagjit Singh, 1928- (Paipasū Buka Ḍipū, 1979)
On the prose style of Teja Singh, 1893-1958, with reference to Sahija subhā